Lipid droplet-associated proteins Perilipin 1 and 2: molecular markers of steatosis and microvesicular steatotic foci in chronic Hepatitis C - Schelbert, Selina; Schindeldecker, Mario; Drebber, Uta; Witzel, Hagen Roland; Weinmann, Arndt; Dries, Volker; Schirmacher, Peter; Roth, Wilfried; Straub, Beate Katharina (International journal of molecular sciences, 2022)
Chronic infection with hepatitis C (HCV) is a major risk factor in the development of cirrhosis and hepatocellular carcinoma. Lipid metabolism plays a major role in the replication and deposition of HCV at lipid droplets (LDs). We have demonstrated the importance of LD-associated proteins of the perilipin family in steatotic liver diseases. Using a large collection of 231 human liver biopsies with HCV, perilipins 1 and 2 have been localized to LDs of hepatocytes that correlate with the degree of steatosis and specific HCV genotypes, but not significantly with the HCV viral load. Perilipin 1- and 2-positive microvesicular steatotic foci were observed in 36% of HCV liver biopsies, and also in chronic hepatitis B, autoimmune hepatitis and mildly steatotic or normal livers, but less or none were observed in normal livers of younger patients. Microvesicular steatotic foci did not frequently overlap with glycogenotic/clear cell foci as determined by PAS stain in serial sections. Steatotic foci were detected in all liver zones with slight architectural disarrays, as demonstrated by immunohistochemical glutamine synthetase staining of zone three, but without elevated Ki67-proliferation rates. In conclusion, microvesicular steatotic foci are frequently found in chronic viral hepatitis, but the clinical significance of these foci is so far not clear.
Gesehen am 30.01.2023